Implementation of Weight Sum Model(WSM) in the Selection of Football Athletes - Lince Tomoria Sianturi (The IJICS (International Journal of Informatics and Computer Science), 2019)
Every soccer team has a standard that is used by coaches in determining athletes that fit the criteria owned by athletes. In this study, researchers used a decision support system (SPK) with the Weight Sum Model (WSM) method, which assesses the results of the criteria needed in the selection of soccer athletes. Decisions made in applying the WSM method will produce recommendations according to the standards used by the trainer. The purpose of this research is to apply the WSM method in selecting soccer athletes based on the desired category. The existence of this system is expected to make selection more objective for trainers in making decisions